NAVIGATING RETENTION RAPIDS: INSIGHTS INTO EMPLOYEE SATISFACTION AND ATTRITION AT PRIVATE UNIVERSITY - Daryl F. Quinco (RADJA PUBLIKA, 2024)
This study presents a comprehensive analysis of employees retention, attrition factors, and partners perceptions at a private university, aiming to provide valuable insights for strategic decision-making and continuous improvement. The research conducted interviews and focus group discussions with partners from both the academic and professional track units of the university. Different themes emerged such as the sense of community, the desire for professional growth, and the commitment to quality education, as retention factors while there are also significant areas of concern which include the high workload, insufficient communication, challenges in work-life balance, and resource limitations. These findings support the recommendation that improving the dedication and motivation of the university's personnel will help it keep them, which will eventually be advantageous to both the school and its students. This research serves as a valuable resource for educational institutions seeking to enhance employee retention and satisfaction in the higher education landscape.